A comparison of methods for the measurement of adherence to antihypertensive multidrug therapy and the clinical consequences: a retrospective cohort study using the Korean nationwide claims database - Jung, Minji; Choo, Eunjung; Lee, Sukhyang (Epidemiology and Health, 2023)
OBJECTIVES: In observational studies, the methods used to measure medication adherence may affect assessments of the clinical outcomes of drug therapy. This study estimated medication adherence to multidrug therapy in patients with hypertension using different measurement methods and compared their impacts on clinical outcomes. METHODS: This was a retrospective cohort study using the Korean National Health Insurance Service–National Sample Cohort database (2006-2015). Adults diagnosed with hypertension who initiated multidrug antihypertensive therapy in the index year 2007 were included. Adherence was defined as over 80% compliance. Adherence to multidrug antihypertensive therapy was measured in 3 ways using the proportion of days covered (PDC) with 2 approaches to the end-date of the study observations: PDC with at least one drug (PDCwith ≥ 1), PDC with a duration weighted mean (PDCwm), and the daily polypharmacy possession ratio (DPPR). The primary clinical outcome was a composite of cardiovascular and cerebrovascular disease-specific hospitalizations or all-cause mortality. RESULTS: In total, 4,226 patients who initiated multidrug therapy for hypertension were identified. The mean adherence according to the predefined measurements varied from 72.7% to 79.8%. Non-adherence was associated with an increased risk of a primary outcome. The hazard ratios (95% confidence intervals, CIs) primary outcomes varied from 1.38 (95% CI, 1.19 to 1.59) to 1.44 (95% CI, 1.25 to 1.67). CONCLUSIONS: Non-adherence to multidrug antihypertensive therapy was significantly associated with an increased risk of a primary clinical outcome. Across the varying estimates based on different methods, medication adherence levels were similar. These findings may provide evidence to support decision-making when assessing medication adherence.
Keywords: Adult; Antihypertensive Agents; Drug Therapy, Combination; Humans; Hypertension; Leprostatic Agents; Republic of Korea; Retrospective Studies; Antihypertensive agent; Combination drug therapy; Therapeutic adherence